Pengaruh Kepemimpinan Kepala Sekolah Dan Budaya Organisasi Terhadap Profesionalisme Guru - Euis Evicasari (LPMP Provinsi DKI Jakarta, 2021)
During Covid-19 pandemic, a teacher is required to adapt. Teacher professionalism requires leaders who can direct and develop in accordance with organizational goals and a conducive working atmosphere. This research to determine the influence of principal leadership and organization culture to teacher professionalism in a public high school. This research is quantitative. Population this study is teachers in 116 high schools, then using the Cluster Sampling 11 schools obtained the population in this study. Total population is 169 teachers. The samples conducted by using the formula Slovin, collected by questionnaire and analyzed with path analysis. The result that leadership have a significantly effecttiveness on the teacher professionalism of 37,4%, the organization culture have a significantly effectiviness on the teacher professionalism of 29,6%, and leadership have a significantly effecttiveness on the organization culture of 17,2%. It can be concluded that leadership and organizational culture have a positive effect on teacher professionalism